Expiratory flow limitation under moderate hypobaric hypoxia does not influence ventilatory responses during incremental running in endurance runners - Cao, Y.; Ichikawa, Y.; Sasaki, Y.; Ogawa, T.; Hiroyama, T.; Enomoto, Y.; Fujii, N.; Nishiyasu, T. (Physiological Reports, 2019)
We tested whether expiratory flow limitation (EFL) occurs in endurance athletes in a moderately hypobaric hypoxic environment equivalent to 2500 m above sea level and, if so, whether EFL inhibits peak ventilation (V_ Epeak), thereby exacerbating the hypoxia-induced reduction in peak oxygen uptake (V_ O2peak). Seventeen young male endurance runners performed incremental exhaustive running on separate days under hypobaric hypoxic (560 mmHg) and normobaric normoxic (760 mmHg) conditions. Oxygen uptake (V_ O2), minute ventilation (V_ E), arterial O2 saturation (SpO2), and operating lung volume were measured throughout the incremental exercise. Among the runners tested, 35% exhibited EFL (EFL group, n = 6) in the hypobaric hypoxic condition, whereas the rest did not (Non-EFL group, n = 11). There were no differences between the EFL and Non-EFL groups for V_ Epeak and V_ O2peak under either condition. Percent changes in V_ Epeak (4 4 vs. 2 4%) and V_ O2peak ( 18 6 vs. 16 6%) from normobaric normoxia to hypobaric hypoxia also did not differ between the EFL and Non-EFL groups (all P > 0.05). No differences in maximal running velocity, SpO2, or operating lung volume were detected between the two groups under either condition. These results suggest that under the moderate hypobaric hypoxia (2500 m above sea level) frequently used for high-attitude training, ~35% of endurance athletes may exhibit EFL, but their ventilatory and metabolic responses during maximal exercise are similar to those who do not exhibit EFL.